Rollout of rapid point of care tests for antenatal syphilis screening in Ghana: healthcare provider perspectives and experiences - Edward Tieru Dassah; Yaw Adu-Sarkodie; Philippe Mayaud (BMC, 2018)
Abstract Background Effective implementation of rapid point of care tests (POCTs) for antenatal syphilis screening especially in settings where antenatal care attendance is high, can significantly increase screening coverage and treatment uptake. The operational challenges of introducing rapid syphilis POCTs at scale needs to be investigated. This study explores healthcare providers' experiences and challenges in antenatal syphilis screening following the national rollout of rapid syphilis POCTs in Ghana. Methods Prior to the main study, we undertook a desk review of key syphilis policy documents, and conducted key stakeholder interviews and a baseline survey of syphilis screening practices. Antenatal syphilis screening had been poorly implemented mainly due to inadequate technical and logistic support, and lack of monitoring and supervision. For the main research, semi-structured interviews were conducted with 51 purposively selected healthcare staff involved in antenatal syphilis screening in 15 health facilities in three regions, representative of all levels of healthcare in Ghana and two regional programme coordinators, at least four months after the rollout. The interviews were supplemented with an audit of the conduct of antenatal care, syphilis-related supplies and other maternal and newborn interventions. Qualitative data were coded and analysed using Nvivo software. Results Syphilis screening with rapid POCTs was integrated into antenatal care in almost all (13/15) the facilities surveyed. Testing and treatment were offered free of charge to pregnant women, their partners and babies. In most facilities, midwives were performing syphilis tests together with HIV tests. Operational challenges included: inadequate training and lack of refresher training, lack of clear testing guidelines, clear channels of communication, supervision, and guidance on treatment and referral procedures, frequent stockouts of, or expired test kits, staff overload, and poor documentation of test results and treatment. Conclusion Although syphilis screening with rapid syphilis POCTs was integrated into antenatal care, key challenges, particularly around supply chain and supervision, need to be addressed to improve and sustain such a programme.